2000
DOI: 10.1016/s0893-133x(99)00162-1
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Olanzapine Occupancy of Muscarinic Acetylcholine Receptors in Patients with Schizophrenia

Abstract: Olanzapine is an atypical antipsychotic with potent antimuscarinic properties in vitro (K i ϭ 2-25 nM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 41 publications
4
32
0
1
Order By: Relevance
“…Since acetylcholine plays an important role in various domains of cognition including attention, it seems reasonable to suggest that changes in the muscarinic receptor system in the ACC in schizophrenia may be involved in the pathology of the disorder, particularly in relation to attentional and cognitive deficits. Most of the atypical antipsychotic drugs (eg clozapine, olanzapine) used for the treatment of both positive and negative symptoms of schizophrenia with less incidence of extrapyramidal side effects have been shown to possess muscarinic antagonistic properties (Raedler et al, 2000). Therefore, abnormalities in the muscarinic receptor system in the ACC in schizophrenia may also be involved in the pharmacotherapy of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since acetylcholine plays an important role in various domains of cognition including attention, it seems reasonable to suggest that changes in the muscarinic receptor system in the ACC in schizophrenia may be involved in the pathology of the disorder, particularly in relation to attentional and cognitive deficits. Most of the atypical antipsychotic drugs (eg clozapine, olanzapine) used for the treatment of both positive and negative symptoms of schizophrenia with less incidence of extrapyramidal side effects have been shown to possess muscarinic antagonistic properties (Raedler et al, 2000). Therefore, abnormalities in the muscarinic receptor system in the ACC in schizophrenia may also be involved in the pharmacotherapy of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, muscarinic receptorcoupled pertussis toxin-sensitive G proteins have been suggested to be the molecular site for the antimanic therapeutic effects of antibipolar treatments (Avissar and Schreiber, 1991). Atypical antipsychotic drugs (eg clozapine, olanzapine), which are among the most effective anti-schizophrenia medications available, have strong antimuscarinic properties (Raedler et al, 2000). Further, studies using post-mortem brain tissue suggest regionspecific changes to muscarinic receptors in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Results from prior studies demonstrate that olanzapine has a high affinity for muscarinic receptors, specifically the M2 autoreceptor (Raedler et al, 2000), and increases acetylcholine release in prefrontal regions (Ichikawa et al, 2002), which may lead to increases in choline. Choline is also precursor and metabolite of membrane phospholipids, such as phosphatidylcholine.…”
Section: Discussionmentioning
confidence: 99%
“…At a daily dose of 20 mg of olanzapine, the muscarinic receptor occupancy was estimated to be 28% in the basal ganglia and 38% in the cortex. 98 In another study using [I-123]-iododexetimide, a different SPECT-ligand for the muscarinic receptors, a substantial occupancy of the muscarinic receptors was confirmed in the striatum and cortex after treatment with olanzapine. 99 Both studies found no relationship between muscarinic receptor availability and side effects.…”
Section: Neuroimaging Studiesmentioning
confidence: 97%